The manifestation of inconclusiveness in King Lear: revaluating dramatic perspectives through irresolution and ambiguity: (Revista Desenredo, 2025)
`This article approaches the sense of inconclusiveness in King Lear manifested in specific dramatic perspectives that engender multiple questions and unresolved conflicts throughout the narrative. Revolving around ambiguous lines and passages, those perspectives occur through an intrinsic correspondence between devices and rhythm as well as the respective confrontation of absolute notions emblematized by the play’s catastrophic ending. Initially, the ambiguity that emanates from the dramatic devices contributes to a growing indeterminacy wherein motivations and questions remain elusive. Following such indeterminacy, any type of pattern is systematically broken as the similarities in the play’s double plot are undermined according to the poignancy of the characters’ sufferings. From another dramatic perspective, the recurrent betrayal of expectations in desolate scenarios guides the events to a point where irresolution dictates the whole pace of the narrative. As the actions are constantly delayed through aimless wanderings and unnecessary interventions, the sense of inconclusiveness is increased and becomes integral with the last scene. Aligned with this sense, the final lines uttered by Lear, Kent, and Edgar evoke a set of passages that emphasize the importance of true feelings even in view of the catastrophic events. Embedded in ambiguity, those lines, at the same time that they reveal the open-ended aspect of the play opposed to its bleak ending, end up disallowing any foreclosed interpretations or conclusive notions.